The children of Taung: Journeying from a rural village to the global stage: The perception of the local community and views regarding the development of the site and the curation of the skull - Mirriam Tawane; Dipuo W. Kgotleng; Bando Baven (South African Journal of Science)
The iconic Taung fossilised skull is widely known for its primacy as Africa’s first palaeoanthropological discovery with universal scientific relevance. Yet the details surrounding its discovery and current status remain an enigma to the community of Taung Village. A comprehensive conservation of the site, which was listed as a UNESCO cultural heritage site of outstanding universal value 25 years ago, is yet to be completed, much to the chagrin of the local communities. The noticeable disconnect between the management authorities and scholarly institutions probably adds to the slow development in regard to continued research and public engagements at the site. In this paper, we discuss the current state of the site and the ongoing development, as well as the knowledge gap and the lack of inclusiveness of the Taung local inhabitants regarding the site.